PENERAPAN KERINGANAN PAJAK KENDARAAN BERMOTOR DIMASA PANDEMI COVID-19 BERDASARKAN PERATURAN GUBERNUR KALIMANTAN TIMUR NOMOR 31 TAHUN 2020 TENTANG KERINGANAN PAJAK KENDARAAN BERMOTOR - Aji Muhammad Doddy Alwanda (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT During the Covid-19 pandemic, the obligation of taxpayers to pay motor vehicle taxes was felt to be very burdensome. Times like this are not only people who feel the impact of covid-19 but the government also experiences the effects of covid-19. To help taxpayers pay motor vehicle tax, the East Kalimantan regional government sees this impact by issuing Governor Regulation Number 31 of 2020 concerning Motor Vehicle Tax Relief. The problem raised in this paper is applying motor vehicle tax relief law based on Governor Regulation Number 31 of 2020 concerning Motor Vehicle Tax Relief and the obstacles in applying motor vehicle tax relief based on Governor Regulation Number 31 of 2020 concerning Motor Vehicle Tax Relief. The type of research used is juridical empirical research, field research with the problem approach used in writing this thesis is a quantitative approach.The results showed that the implementation of the motor vehicle tax relief policy in East Kalimantan Province during the Covid-19 pandemic succeeded in attracting taxpayers' attention to make motor vehicle tax payments. The lack of socialization of motor vehicle tax relief and less understanding, taxpayers paying motor vehicle taxes online are an obstacle to the application of vehicle tax breaks. Keywords: Law Application, Motor Vehicle Tax.